Synthesis, Physico-Chemical and Antimicrobial Studies of Ionic Liquid - I. Al-Resayes, Saud; Ali Khan, Azmat; Azam, Mohammad; Trzesowska-Kruszynska, Agata; Kruszynski, Rafal; Oves, M. (Asian Journal of Chemistry, 2014)
A novel ammonium salt, an ionic liquid (ILs) was synthesized at room temperature. Its structure was elucidated by elemental analyses and various spectroscopic techniques like FT-IR, 1H and 13C NMR and ESI-MS spectrometry. Thermal studies were also carried out to get thermal stability of the ionic compound. X-ray crystallographic study was carried out to ascertain the structure of ammonium cation which is bonded to three anion via O–H…Cl intermolecular hydrogen bonds. Synthesized compound was also investigated for in vitro antimicrobial study against number microbes and results showed excellent results.